Avaliação do status sanitário do rebanho suíno do Estado do Maranhão em relação a peste suína clássica e a leptospirose: estudo imunológico e de biologia celular - Galvão, Giselle Mesquita de França (2016)
This study aimed to evaluate the health status of the herd swine in the state of Maranhão related with the Classical Swine Fever (CSF) and Leptospirosis. It was collected three hundred (300) blood samples and one hundred (100) tonsil fragments for research Classical Swine Fever and 190 (one hundred and ninety) blood samples selected in random order for leptospirosis research, distributed in 15 (fifteen) municipalities: Açailandia, Bom Jesus das Selvas, Formosa da Serra Negra , Fortaleza dos Nogueiras, Barra do Corda, Caixas, Peritoró, Coroatá, Imperatriz, São Luís, Sâo José de Ribamar, Paço do Lumiar, Bequimão and São Bento. The Blood samples relative Classical Swine Fever research were submitted to the test of Enzyme-Linked Immunosorbent Assay (ELISA) and samples of tonsil fragments for RT-PCR. For the research of leptospirosis was made proof Micróspica agglutination test (MAT), and was used 24 serovars of Leptospira spp anti-complex. Of the 300 (100%) blood samples and 100 (100%) tonsil samples, all (100%) were negative. Of the 190 (100%) specimens tested by SAM, 79 (41.58%) were positive for one or more serovars used in 1:100 dilution. The most frequent was serovars Canicola 29\190 (15.3%), followed by Sentot 26\190 (13.9%), Butembo 22\190 (11.6%), Tarassovi 19\190 (10%), Whitcombi 16\190 (8.4%), and Batavae 13\190 (6,8%) . The absence of viral circulation in these environments provides subsidies that help to support the state for the eradication of Classical Swine Fever. Regarding Leptospirosis, positivity reflects the need for measures to be taken to control this disease